New Research at the Gymnasium of Agrigento - Trümper, Monika; Kay, Stephen; Pomar, Elena; Fino, Antonello; Lappi, Thomas; Santospagnuolo, Paola (Archäologischer Anzeiger, 2022)
The gymnasium of Agrigento is one of the most important, if not the most important gymnasium in Sicily and the western Mediterranean more generally, because of its size, design, and chronology. While parts of a race-track section and a pool were excavated between the 1950s and 2005 and were published in 2009 and 2011, crucial questions remain open: the extension, design, and most notably the existence and location of a palaestra; the construction date in the 2nd century B.C. or the Augustan period; and the urban context. To answer these questions, a project was launched in 2019 in cooperation between the Parco Archeologico e Paesaggistico Valle dei Templi di Agrigento and the Freie Universität Berlin, and a first season, together with the British School at Rome, was carried out in 2020. This paper presents the results of this first campaign, which included first, a geophysical survey of the area around the gymnasium and of a field to the north of the Hellenistic-Roman temple; and second, an architectural survey of unpublished features and work in the archives and storerooms of the Parco Archeologico.